Analisis laporan keuangan Bank Panin Dubai Syariah melalui pendekatan rasio Return on Assets (ROA): Studi kasus Laporan tahun 2020-2024 - Asqolani, Ahmad Maulana Kholil Muhajir Madani (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the profitability level of Panin Dubai Syariah Bank (PDSB) using the Return on Assets (ROA) ratio approach during the 2020–2024 period. The analysis was conducted to determine the bank's effectiveness in utilizing total assets to generate net profit. The financial statements show significant fluctuations in ROA values, with a downward trend in 2020–2023 and a rebound in 2024. Based on the calculation results, ROA decreased from 1.133% (2020) to 0.141% (2023) before increasing to 0.527% in 2024, although net profit and total assets showed varying patterns of change. The decline in ROA for most of the period reflects pressure on operational efficiency, possible cost increases, and potential financing issues. Meanwhile, the increase in ROA in 2024 indicates improved efficiency despite declining assets. These findings indicate that effective asset management is a critical factor in the profitability of Islamic banks and should be a primary focus of management.